Biodegradation of Simazine and Diuron Herbicides under Aerobic and Anoxic Conditions Relevant to Managed Aquifer Recharge of Storm Water. Issue 6 (28th October 2013) - Shareef, Ali; Page, Declan; Vanderzalm, Joanne; Williams, Mike; Gupta, V. V. S. R.; Dillon, Peter; Kookana, Rai
<x xml:space="preserve">Abstract</x> The fate of simazine and diuron during natural treatment processes occurring in aquifers during managed aquifer recharge (MAR) was evaluated by batch tests in conditions relevant to MAR using urban storm water. The tests were performed with aquifer sediment and wetland treated storm water under aerobic and anoxic geochemical conditions, with and without a carbon source amendment to assess the degradation of these herbicides. The aerobic conditions were suited for the relatively rapid degradation of the positive control 17β‐estradiol with a half‐life of 3.8–4.5 days and a much slower decay of simazine (30–32 days) and diuron (35–41 days). The study also showed that significant attenuation of simazine can be achieved through biodegradation under nitrate reducing conditions in aquifer sediments, with a similar half‐life (26–30 days) to the aerobic condition. The biodegradation half‐life of diuron under nitrate reducing conditions was long (91 days), but carbon supplement (20 mg C/L) halved it to 41 days. Significant attenuation of simazine and diuron in aquifers may be achievable, if sufficient residence time (e.g. at least a year) is allowed in the subsurface in aquifer storage, transport and recovery schemes.